Analisis Faktor Risiko Kejadian Stunting Pada Anak Balita Di Wilayah Puskesmas Kelurahan Cipinang Melayu Jakarta Timur - Florensia Herianti; Elwindra Elwindra (STIKes Persada Husada Indonesia, 2017)
The national stunting prevalence of 37.2% is included in the serious public health problem. Stunting risk factors include patterns of parenting, infectious diseases such as diarrhea and Upper Respiratory Tract Infection, birth weight, and Exclusive breastfeeding. This study aims to determine the risk factors of stunting incidence in children under five that is done in the Work Area Puskesmas Kelurahan Cipinang Melayu East Jakarta Year 2017. The design of this study is quantitative with Cross Sectional approach. The population in this study is children aged 12-59 months old who are in the Area Puskesmas Kelurahan Cipinang Melayu East Jakarta. Samples were taken with Purposive Sampling method of 60 infants, with 30 toddlers who were stunting as a case and 30 children were not stunting as control. Data were collected by filling the questionnaire, then statistical test with chi square. In this study most respondents at the age of 24-35 months (33.3%), Sex Male (55.0%), Birth weight <3 kg (55.0%), Breast Milk Not Exclusive (61,7% %). And the respondent had good child care pattern (70.0%), infant rarely affected by infectious diseases (55.0%), and had received and utilized health service well (50,0%). Results of Bivariate Analysis found that the variables associated with the incidence of stunting were Exclusive Breastmilk with P-value value 0.017 and OR value = 3.755. This suggests a significant relationship between the exclusive breastfeeding variable and the stunting event, that exclusive breastfeeding reduces the risk of stunting incidence in infants by 3.755 times compared with those not exclusively breastfed. The results of statistical test also found a significant relationship between Health Service variables with stuntig events, with P-Value value 0,039 and OR = 0,335, indicating that Good Health Service will reduce the risk of stunting incidence in children by 0,335 times compared to those who get Health Service not good.